Kesejahteraan Psikologis Pada Narapidana Perempuan di Lapas IIA Jember - Sinta Maharani; Arrumaisha Fitri (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
The life that a prisoner lives while in prison causes prisoners to face various psychological problems, including loss of family, loss of self- control, and loss of support. The aim of this research: First, to describe the psychological well-being of female prisoners at Prison II A Jember. Second, to describe the impact of psychological well-being on the activities of female prisoners at Prison II A Jember. This research is qualitative research with a field study approach. The technique for determining research subjects uses purposive techniques, while the data collection technique uses observation, interviews and documentation. The data validity test used is source triangulation and technical triangulation. The conclusions from this research are as follows: The description of the psychological well-being of female prisoners at Prison II A Jember shows that there are still obstacles that hinder the fulfillment of optimal psychological well-being. Factors supporting the psychological well-being of female prisoners are social support, positive interactions and spirituality. Meanwhile, factors inhibiting psychological well-being are personality, cultural differences,, and infrastructure.